In Vitro Susceptibility of Ciprofloxacin‐Resistant Methicillin‐Resistant Staphylococcus aureus to Ototopical Therapy. (13th March 2018) - Walker, David D.; David, Michael Z.; Catalano, Dominic; Daum, Robert; Gluth, Michael B.
Abstract : Objective: Despite the rising incidence of methicillin‐resistant Staphylococcus aureus (MRSA) otologic infections, choice of treatment remains controversial. Only fluoroquinolone‐containing ototopical preparations are approved by the US Food and Drug Administration for middle ear application. Furthermore, American Academy of Otolaryngology–Head and Neck Surgery Foundation guidelines advocate ototopical monotherapy for both tympanostomy tube otorrhea and acute otitis externa. Unfortunately, MRSA may be ciprofloxacin resistant. This causes confusion regarding antibiotic selection, because susceptibility profiles reflect a minimum inhibitory concentration (MIC), referenced against systemic, not ototopical, drug delivery dosing. The goal of this study is to determine the ciprofloxacin MIC for ciprofloxacin‐resistant MRSA isolates from otologic infections and compare that value to the expected drug concentration achieved by fluoroquinolone ear drops and determine MRSA genotype for each isolate. Study Design: In vitro assay with retrospective medical record review. Setting: Tertiary care university hospital. Subjects and Methods: Thirty otologically sourced ciprofloxacin‐resistant MRSA isolates collected from adult and pediatric patients. MICs were calculated by broth dilution method. Isolates underwent multilocus sequence typing and polymerase chain reaction for arcA and Panton‐Valentine leukocidin to establish the genotype. Results: MICs ranged from 16 to 1025 µg/mL. There was a relationship between MIC and genotype; of the 7 isolates with an MIC value greater than 512 µg/mL, 6 were sequence type (ST)8. Conclusion: These findings support the practice of ototopical monotherapy for patients with uncomplicated ciprofloxacin‐resistant MRSA otitis externa. However, they raise concern that ototopical therapy may not be adequate to treat highly resistant strains of MRSA infecting the middle ear space.